Literary and Scholarly Reputation. About the book Izmailov, A.A.: Correspondence with Contemporaries - Elena V. Khvorostianova (Studia Litterarum)
The book, prepared under the general editorship of A.S. Alexandrov, presents correspondence of one of the most authoritative critics and participants of the literary and social life of St. Petersburg in the early 20th century — A.A. Izmailov and his contemporaries. The main contribution of this book is the introduction of the vast, hitherto unpublished material. However the unmotivated selection of letters and correspondence for publication, incorrect comments and violation of accepted editorial principles reduce the value of the book aimed at general audience